Tutela internacional das áreas úmidas sul-americanas : instrumentos de proteção do Pantanal e do Chaco - Lima, Diogo Marcelo Delben Ferreira de (2014)
The environmental issue of concern to the international community, promoting significant changes in contemporary legal systems. The degradation of natural areas and biodiversity erosion force the adoption of legal instruments and policy measures for environmental protection. The wetlands of South America, located in the northern portion of the continent, in the territories of Brazil and Bolivia (and other) environments are of ecological and humanitarian law. The aim of this work is to analyze the fundamentals of law and international politics and rules of law applicable to humid environments and Pantanal in South America The research adopts the method monist internationalist dialogical, plural considering the possibilities of interpretation and application of law, from the perspective of interaction of the sources of law and to give best solution to the challenge post. Those countries in the light of Latin American constitutionalism, have developed the constitutional protection of the environment and made available significant legal basis in order to affirm the fundamental ecological rights. International instruments, such as the Ramsar Convention and the Treaty on the River Plate Basin, contribute to the effectiveness of the " international law of wetlands in South America ."